Phosphorus Uptake by Potato from Fertilizers Recovered from Anaerobic Digestion. (1st September 2016) - Collins, Harold P.; Kimura, Emi; Frear, Craig S.; Kruger, Chad E.
Abstract : The rising costs of fertilizers have encouraged the development of technologies to recover nutrients from dairy, cattle, swine, and poultry operations. Field experiments were conducted in the Columbia Basin of Washington to assess the yield of potato ( Solanum tuberosum L.) to application of P‐enriched materials recovered from anaerobic digestion of manure. Four rates of P from five sources, three recovered from anaerobic digesters (AD), AD‐dairy P‐enriched fine solids (ADD), AD centrifuged poultry solids (ADP), and AD dairy struvite‐P (ADS) compared to a commercial poultry fertilizer (PBP) were compared to mono‐ammonium phosphate (MAP) and non‐amended control (No‐P). Fertilized treatments had higher yields than the No‐P treatment. Phosphorus source and application rate had significant effects on petiole P concentrations. Increases in petiole P concentrations averaged 300 to 500 mg kg −1 tissue with each rate increase for MAP and ADS. Tuber yields among P fertilizers and rates of P application were not significant but were different between years, averaging 2 and 10 Mg ha −1 fresh weight higher than the No‐P treatment. Tuber size distribution showed a significant shift from smaller tubers <170 g to the 285+ g tuber classes. The P recovery efficiency averaged 42% among treatments receiving 56 kg P2 O5 ha −1 and declined to 22% for higher rates of ADS, ADD, and MAP. Recoveries were lowest for poultry derived materials, ranging 20 to 30%. The P fertilizer sources evaluated performed similarly when equal rates of P were applied and method of application was comparable. Phosphorus recovered from anaerobic digesters can effectively substitute for commercial mined P fertilizers. Potato yields among recovered P fertilizers and rates of P application were not significantly different. Recovered P fertilizer performed similarly when equal rates were applied and method of application was comparable.